Chiral multifunctional thiourea-phosphine catalyzed asymmetric [3 + 2] annulation of Morita–Baylis–Hillman carbonates with maleimides - Deng, Hong-Ping; Wang, De; Wei, Yin; Shi, Min (Beilstein Journal of Organic Chemistry, 2012)
We have developed a multifunctional thiourea-phosphine catalyzed asymmetric [3 + 2] annulation of Morita–Baylis–Hillman (MBH) carbonates with maleimides, which can efficiently construct functionalized cyclopentenes bearing three contiguous stereocenters in moderate to excellent yields and excellent diastereo- and enantioselectivities. A plausible mechanism has been also proposed on the basis of control experiments and previous literature.
Keywords: asymmetric [3 + 2] annulation; maleimides; Morita–Baylis–Hillman carbonates; multifunctional thiourea-phosphine; organocatalysis

(untitled) - Hartley, R. C.; Caldwell, S. T. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Wu, H.; Zhang, H.; Zhao, G. (Tetrahedron, 2007)

(untitled) - Lu, X.; Zhang, C.; Xu, Z. (Acc. Chem. Res., 2001)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Ye, L.-W.; Zhou, J.; Tang, Y. (Chem. Soc. Rev., 2008)

(untitled) - Cowen, B. J.; Miller, S. J. (Chem. Soc. Rev., 2009)

(untitled) - Marinetti, A.; Voituriez, A. (Synlett, 2010)

(untitled) - Wei, Y.; Shi, M. (Acc. Chem. Res., 2010)

(untitled) - López, F.; Mascareñas, J. L. (Chem.–Eur. J., 2011)

(untitled) - Zhao, Q.-Y.; Lian, Z.; Wei, Y.; Shi, M. (Chem. Commun., 2012)

(untitled) - Zhang, C.; Lu, X. (J. Org. Chem., 1995)

(untitled) - Xu, Z.; Lu, X. (J. Org. Chem., 1998)

(untitled) - Xu, Z.; Lu, X. (Tetrahedron Lett., 1999)

(untitled) - Du, Y.; Lu, X. (J. Org. Chem., 2003)

(untitled) - Lu, Z.; Zheng, S.; Zhang, X.; Lu, X. (Org. Lett., 2008)

(untitled) - Zheng, S.; Lu, X. (Org. Lett., 2008)

(untitled) - Du, Y.; Lu, X.; Zhang, C. (Angew. Chem., Int. Ed., 2003)

(untitled) - Zhu, X.-F.; Lan, J.; Kwon, O. (J. Am. Chem. Soc., 2003)

(untitled) - Tran, Y. S.; Kwon, O. (J. Am. Chem. Soc., 2007)

(untitled) - Na, R.; Jing, C.; Xu, Q.; Shi, J.; Jiang, H.; Wu, X.; Shi, J.; Zhong, J.; Wang, M.; Benitez, D.; Tkatchouk, E.; Goddard, W. A., III; et al. (J. Am. Chem. Soc., 2011)

(untitled) - Zhu, G.; Chen, Z.; Jiang, Q.; Xiao, D.; Cao, P.; Zhang, X. (J. Am. Chem. Soc., 1997)

(untitled) - Wurz, R. P.; Fu, G. C. (J. Am. Chem. Soc., 2005)

(untitled) - Wilson, J. E.; Fu, G. C. (Angew. Chem., Int. Ed., 2006)

(untitled) - Fujiwara, Y.; Fu, G. C. (J. Am. Chem. Soc., 2011)

(untitled) - Mercier, E.; Fonovic, B.; Henry, C.; Kwon, O.; Dudding, T. (Tetrahedron Lett., 2007)

(untitled) - Voituriez, A.; Panossian, A.; Fleury-Brégeot, N.; Retailleau, P.; Marinetti, A. (J. Am. Chem. Soc., 2008)

(untitled) - Voituriez, A.; Panossian, A.; Fleury-Brégeot, N.; Retailleau, P.; Marinetti, A. (Adv. Synth. Catal., 2009)

(untitled) - Voituriez, A.; Pinto, N.; Neel, M.; Retailleau, P.; Marinetti, A. (Chem.–Eur. J., 2010)

(untitled) - Han, X.; Wang, Y.; Zhong, F.; Lu, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Han, X.; Wang, S.-X.; Zhong, F.; Lu, Y. (Synthesis, 2011)

(untitled) - Han, X.; Zhong, F.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2012)

(untitled) - Cowen, B. J.; Miller, S. J. (J. Am. Chem. Soc., 2007)

(untitled) - Fang, Y.-Q.; Jacobsen, E. N. (J. Am. Chem. Soc., 2008)

(untitled) - Xiao, H.; Chai, Z.; Zheng, C.-W.; Yang, Y.-Q.; Liu, W.; Zhang, J.-K.; Zhao, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Sampath, M.; Loh, T.-P. (Chem. Sci., 2010)

(untitled) - Steurer, M.; Jensen, K. L.; Worgull, D.; Jørgensen, K. A. (Chem.–Eur. J., 2012)

(untitled) - Xiao, H.; Chai, Z.; Wang, H.-F.; Wang, X.-W.; Cao, D.-D.; Liu, W.; Lu, Y.-P.; Yang, Y.-Q.; Zhao, G. (Chem.–Eur. J., 2011)

(untitled) - Du, Y.; Feng, J.; Lu, X. (Org. Lett., 2005)

(untitled) - Feng, J.; Lu, X.; Kong, A.; Han, X. (Tetrahedron, 2007)

(untitled) - Zheng, S.; Lu, X. (Tetrahedron Lett., 2009)

(untitled) - Zheng, S.; Lu, X. (Org. Lett., 2009)

(untitled) - Ye, L.-W.; Sun, X.-L.; Wang, Q.-G.; Tang, Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Han, X.; Ye, L.-W.; Sun, X.-L.; Tang, Y. (J. Org. Chem., 2009)

(untitled) - Zhou, R.; Wang, J.; Song, H.; He, Z. (Org. Lett., 2011)

(untitled) - Chen, Z.; Zhang, J. (Chem.–Asian J., 2010)

(untitled) - Xie, P.; Huang, Y.; Chen, R. (Org. Lett., 2010)

(untitled) - Tian, J.; Zhou, R.; Sun, H.; Song, H.; He, Z. (J. Org. Chem., 2011)

(untitled) - Wang, Q.-G.; Zhu, S.-F.; Ye, L.-W.; Zhou, C.-Y.; Sun, X.-L.; Tang, Y.; Zhou, Q.-L. (Adv. Synth. Catal., 2010)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Adv. Synth. Catal., 2012)

(untitled) - Shi, Y.-L.; Shi, M. (Adv. Synth. Catal., 2007)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Eur. J. Org. Chem., 2011)

(untitled) - Yang, Y.-L.; Pei, C.-K.; Shi, M. (Org. Biomol. Chem., 2011)

(untitled) - Deng, H.-P.; Shi, M. (Eur. J. Org. Chem., 2012)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Org. Lett., 2011)

(untitled) - Ito, M.; Osaku, A.; Kobayashi, C.; Shiibashi, A.; Ikariya, T. (Organometallics, 2009)

(untitled) - Jiang, Y.-Q.; Shi, Y.-L.; Shi, M. (J. Am. Chem. Soc., 2008)

(untitled) - Plietker, B.; Niggemann, M. (Org. Lett., 2003)